Pengembangan Aplikasi E-Book Elektrokimia Berbasis Android Untuk Menumbuhkan Self-Directed Learning Mahasiswa - Rahmat Rasmawan*; Erlina Erlina (Universitas Syiah Kuala, 2021)
Students' weak ability to understand electrochemical concepts is due to the lack of self-directed learning (SDL) in finding their own understanding outside the classroom and not used to evaluate the learning difficulties they experienced. The android-based e-books could be used to support students’ independent learning, to evaluate learning outcomes through practice questions and direct feedback, and to exchange opinions between students and lecturers. The aim of this study is to produce an android-based electrochemical e-book to emerge students’ SDL. To achieve the aim, this study employs ADDIE development models which consist of five steps; analyze, design, develop, implement and evaluate. Data were collected using content validity, face validity assessment, response questionnaires and SDL. The result of content validity is 0.94 and categorized as valid. Based on face validity, vast majority of users stated that the e-book application is attractive and easy to use. Moreover, the explanation, graphics, videos, quiz questions and discussion in the e-book application are clear. The results of the implementation of application as additional learning resource for electrochemical concepts can foster students’ SDL in the high category with an average percentage of confidence at 87.20%. Students show a positive response to the use of the application in helping them understand the concepts, working on assignments, discussions between friends and lecturers, digging more in-depth information, and do practice questions in a short time, also easy to use. Thus, it can be concluded that the android-based e-book application could help students develop their SDL